Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1186/s12883-023-03314-3
|View full text |Cite
|
Sign up to set email alerts
|

Stroke in women: experience in a developing country

Abstract: Background Several studies have addressed gender differences in stroke. Yet, results are diverse, and research is still required in different populations. So, this study investigates variation in stroke according to gender in a developing country. Methods This is a registry-based, retrospective observational cross-sectional study comparing men and women as regards age, risk factors, stroke severity, quality of services, and stroke outcome. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 63 publications
1
0
0
Order By: Relevance
“…Stroke is a prevalent disease worldwide, and dysphagia, a common complication of stroke, is significantly associated with a reduced QOL ( 23 ). Our study found that female stroke patients had better QOL than males, and urban participants had better QOL compared to their rural counterparts, consistent with prior research findings ( 24 , 25 ). Under these circumstances, investigating the impact of stroke-related dysphagia on QOL and its underlying mechanisms is of great practical significance for healthy aging and patient well-being.…”
Section: Discussionsupporting
confidence: 92%
“…Stroke is a prevalent disease worldwide, and dysphagia, a common complication of stroke, is significantly associated with a reduced QOL ( 23 ). Our study found that female stroke patients had better QOL than males, and urban participants had better QOL compared to their rural counterparts, consistent with prior research findings ( 24 , 25 ). Under these circumstances, investigating the impact of stroke-related dysphagia on QOL and its underlying mechanisms is of great practical significance for healthy aging and patient well-being.…”
Section: Discussionsupporting
confidence: 92%